Referring academic library chat reference patrons: how subject librarians decide - Dempsey, Paula R (Reference services review, 2021)
Purpose The purpose of this study is to learn what factors liaison librarians in academic research libraries consider in determining whether to refer chat reference patrons to subject specialists. Design/methodology/approach Subject specialists were asked what policies guided their decisions to refer to a specialist and then assessed unreferred chat session transcripts both within and outside their specializations to determine need for a referral. Findings Few respondents were guided by formal policies. Contrary to an initial hypothesis, subject area was not a key factor in referring chat. A broader set of criteria included reference interviewing, provision of relevant resources and information literacy instruction. Respondents valued both the depth that subject specialists can provide to reference interactions and the ability of a skilled generalist to support information literacy. Research limitations/implications Findings are most applicable to large, public doctoral universities with liaison librarian programs. Assignment of respondents to subject specialist categories was complicated by their broad range of background and expertise. Practical implications The study contributes new understanding of referrals to subject specialists who have potential to guide development of formal referral policies in academic library virtual reference services. Originality/value The study is the first empirical examination of chat reference referral decisions.